Opportunities to Develop Enterpreneurial-Based Development Economy in The Era of Globalization - Andi Cudai Nur; Slamet Riadi Cante; Risma Niswaty (Iapa Proceedings Conference, 2020)
This study aims to look at how entrepreneurship in tourism captures opportunities in the Covid-19 phenomenon that is endemic in Indonesia, and explains the essence and orientation of opportunities to develop the potential of leading entrepreneurship-based tourism. The approach used is quantitative and qualitative techniques, related to philosophical considerations, the application of quantitative and qualitative approaches, and the mixing of these two studies in one study. The results showed: 1. Tourism potential in Sinjai Regency, 2. The development of local and foreign tourists in Sinjai Regency. Tourism potential and tourism development in Sinjai need to be supported by the tourism industry based on entrepreneurship in each tourist destination, through several functions, such as preparing various breakthroughs in preparing and overcoming various unexpected problems both now and in the future, such as: regulating the tourism industry by planning activities operational and procedures in carrying out activities with international standards by formulating standardization policies, recommendations and technical guidance, evaluation, reporting and implementation in the development of the tourism industry, also provides professional facilities in the tourism industry with guidance and technical guidance for tourism businesses regarding standardization, norms, criteria and verification, ease of business by mapping and promoting business investment in the tourism industry through coordination, cooperation, in the context of smooth implementation of tasks. Local governments, entrepreneurs and the wider community are expected to capture the various opportunities available to increase sources of income in supporting development.